KONSEP KESAKRALAN MIRCEA ELIADE DALAM TRADISI PERINGATAN MALAM SATU SURO DI KOTAGEDE YOGYAKARTA - Yuwono, Adhimas Alifian; Nurhuda, Abid; Ansori, Inamul Hasan (Pascasarjana Universitas Hindu Indonesia, 2024)
This article aims to show the representation of Mircea Eliade's concept of